2016
DOI: 10.1103/physrevc.94.064322
|View full text |Cite
|
Sign up to set email alerts
|

μs isomers of Nd158,160

Abstract: The neutron-rich nuclei 158,160 Nd have been studied via delayed γ -ray spectroscopy of μs isomeric states at the RIBF facility, RIKEN. These nuclei were produced following the projectile fission of a 345 A MeV 238 U beam and delayed γ rays were detected by the EURICA cluster Ge array. The isomeric states have measured half-lives of 339 (20)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In Fig. 18 the systematic behavior of the Z = 62 and N = 100 E1 reduced hindrances is shown, using the present values and those from the literature [3,5,7,8,10,11,32]. The inclusion of the 10 4 factor makes the K = 5 (Z = 62) values closer to those for K = 4 (N = 100).…”
Section: E1 Reduced Hindrance Factorsmentioning
confidence: 57%
See 1 more Smart Citation
“…In Fig. 18 the systematic behavior of the Z = 62 and N = 100 E1 reduced hindrances is shown, using the present values and those from the literature [3,5,7,8,10,11,32]. The inclusion of the 10 4 factor makes the K = 5 (Z = 62) values closer to those for K = 4 (N = 100).…”
Section: E1 Reduced Hindrance Factorsmentioning
confidence: 57%
“…Isomers in deformed nuclides are most abundant in the A ∼ 180 region above midshell [2][3][4], but there have been several recent discoveries in the midshell region and below, i.e., in the neutron-rich, A = 160-170 region, exploiting mass-separated isomeric beams, e.g., Refs. [5][6][7][8][9][10]. In such cases, the existence of high-spin isomers provides a useful tool to probe the excited-state structure of nuclei that are otherwise difficult to populate.…”
Section: Introductionmentioning
confidence: 99%
“…[633] orbital, like two-neutron 6 − state in 160 Sm and 4 − state in 162 Sm, reproduce the experimental data well, the disagreement of the two-neutron 6 − state in 164 Sm is mainly caused by the upward shift of the ν 5 [512] orbital with non-zero ε6 . This indicates that the energy gap at N = 102 should be smaller.…”
mentioning
confidence: 53%
“…The nuclear structure inputs of the rare-earth nuclei can lead to an improved understanding of the r−process nucleosynthesis [3]. However, due to their neutron excess, detailed structure informations are very difficult to be revealed by the experiment in these rare-earth neutron-rich nuclei.The recent experimental progresses in the neutron-rich A = 150 − 170 region [4][5][6][7][8][9][10][11][12][13] are attributed to a great extent to the existence of the nuclear isomeric state. A nucleus can be "traped" in an aligned spin orientation relative to its symmetric axis to form the K isomeric state (or K-isomer), where K is a quantum number representing the projection of the total nuclear spin along the symmetry axis of the nucleus.…”
mentioning
confidence: 99%
“…Several years after, the observation was extended to N = 102 in Sm and Gd isotopic chains using in-flight fission, and a local maximum of the ground-band energies was revealed at N = 100 which seemingly indicated the predicted deformed shell gap at N = 100 [14]. Following studies discovered the 4 − ν(7/2[633] ⊗ 1/2[521]) isomers in the N = 100 isotones from Z = 60 to 64 [15,16] and found that their excitation energies and hindrance factors are not significantly different from those in the stable 68 Er and 70 Yb isotones. This means the energy space between the ν7/2[633] and ν1/2 [521] orbitals at N = 100 is stable against the change of the proton number from 60 to 70 [16], which can be explained without the appearance of the N = 100 deformed shell gap around Z ≈ 62.…”
mentioning
confidence: 99%